Robust TiO2/BDD heterojunction photoanodes for determination of chemical oxygen demand in wastewaters - Han, Yanhe; Qiu, Jingxia; Miao, Yuqing; Han, Jisheng; Zhang, Shanqing; Zhang, Haimin; Zhao, Huijun (Analytical methods, 2011)
A TiO₂/BDD heterojunction photoanode, utilizing the inherent properties of nanostructured titanium dioxide (TiO₂) and boron-doped diamond (BDD), was prepared and used to determine chemical oxygen demand (COD) in wastewaters. The TiO₂ nanoparticles were dip-coated on a BDD substrate and subject to calcination processes. A uniform, continuous and robust mixed-phase (anatase and rutile) TiO₂/BDD heterojunction electrode was obtained. The TiO₂/BDD heterojunction electrode was evaluated using a series of materials characterisation, electrical and electrochemical techniques. The preliminary results suggest the elevated photoelectrocatalytic activity over the oxidation of organic compounds stemmed from the formation of the p–n junction of the TiO₂/BDD electrode. The TiO₂/BDD electrode has an excellent resistance towards strong acid due to the use of BDD substrate, which is an added advantage for practical application. Under the optimized experimental conditions, the TiO₂/BDD electrode is capable of indiscriminately oxidizing a wide spectrum of organic compounds in a photoelectrochemical thin-layer cell. This bestows the photoelectrochemical system with the ability to measure the COD of synthetic and real samples in a fast, sensitive, reproducible and accurate fashion. In particular, a typical analysis time of 5 minutes, a practical detection limit of 0.12 mg L⁻¹ COD, a RSD% value of 1.5% and a linear range of 0–300 mg L⁻¹ were achieved. The TiO₂/BDD electrode can be an ideal sensor for online and in situ monitoring of organic pollutants in wastewaters.